2005
DOI: 10.1080/00498250400021804
|View full text |Cite
|
Sign up to set email alerts
|

AhR and PPARa: antagonistic effects on CYP2B and CYP3A, and additive inhibitory effects on CYP2C11

Abstract: The aryl hydrocarbon receptor (AhR) is a ligand-activated transcription factor that mediates a spectrum of toxic and biological effects of 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) and related compounds. The peroxisome proliferator-activated receptor alpha (PPARalpha) is a member of the nuclear receptor super-family of ligand-activated transcription factors and it functions as an obligate heterodimer with retinoid X-receptor alpha RXRalpha. The aim was to investigate whether the negative cross-talk recently p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
17
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 56 publications
6
17
0
Order By: Relevance
“…CAR was induced by EMD, correlating with strong increases in Cyp2B mRNA expression in rats in vivo and in vitro. It has been previously reported that PPAR␣ agonists have the potential to induce Cyp2B and lead to the suppression of Cyp2C11 in rats both on protein and mRNA levels (Shaban et al, 2005), further confirming that EMD is a potent PPAR␣ agonist in rats. In monkeys, CYP2B6 was repressed after 4 weeks and remained unchanged after 17 weeks.…”
Section: Discussionsupporting
confidence: 56%
“…CAR was induced by EMD, correlating with strong increases in Cyp2B mRNA expression in rats in vivo and in vitro. It has been previously reported that PPAR␣ agonists have the potential to induce Cyp2B and lead to the suppression of Cyp2C11 in rats both on protein and mRNA levels (Shaban et al, 2005), further confirming that EMD is a potent PPAR␣ agonist in rats. In monkeys, CYP2B6 was repressed after 4 weeks and remained unchanged after 17 weeks.…”
Section: Discussionsupporting
confidence: 56%
“…Mechanisms of AHR-mediated induction of P450s are partly understood as they have been studied extensively; however, our understanding of P450 suppression is less clear (Riddick et al, 2004). Data from our laboratory (Jones and Riddick, 1996), in agreement with earlier studies (reviewed in Riddick et al, 2003) as well as recent studies (Caron et al, 2005;Shaban et al, 2005), show that exposure of male rats to aromatic hydrocarbons results in the suppression of hepatic CYP2C11 catalytic activity, protein, and mRNA levels via an unknown pretranslational mechanism.…”
supporting
confidence: 81%
“…However, the effects on the expression of CYP arachidonic acid-epoxygenases appear to vary in different tissues. In rats, treatment with fibrates reduced the level of CYP2C11 expression in the liver (21,130,141). This effect could be recapitulated in cultured hepatocytes, but only when the cells were transfected with PPAR␣.…”
Section: Effects Of Ppar␣ Activation On Eet Production and Metabolismmentioning
confidence: 87%